(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2018)
Science process skills are considered as one of the momentous learning goals for a pre-service education program, but since students enrolled in pre-service elementary school teachers program comes from a different educational background, we evaluated whether the implementation of experiment learning and educational background might lead to a different level of success in science process skills acquisition. Results showed that different learning methods, as well as different educational background, resulted in different science process skills improvement.